Cellular reactive oxygen species inhibit MPYS induction of IFNβ. - Lei Jin; Laurel L Lenz; John C Cambier (PLoS ONE)
Many inflammatory diseases, as well as infections, are accompanied by elevation in cellular levels of Reactive Oxygen Species (ROS). Here we report that MPYS, a.k.a. STING, which was recently shown to mediate activation of IFNβ expression during infection, is a ROS sensor. ROS induce intermolecular disulfide bonds formation in MPYS homodimer and inhibit MPYS IFNβ stimulatory activity. Cys-64, -148, -292, -309 and the potential C₈₈xxC₉₁ redox motif in MPYS are indispensable for IFNβ stimulation and IRF3 activation. Thus, our results identify a novel mechanism for ROS regulation of IFNβ stimulation.